41 Optimization of an ultrasensitive, quantitative immunoassay for detection of CD20 in non-hodgkin's lymphoma (NHL) FFPE samples. (9th November 2020) - Goel, Apollina; Ross, Michael; Rheinhardt, Jeanette; Duval, Peter; Maker, Michael; Yokota, Hiroyuki; Bloom, Kenneth; Abe, George; Ranger, Ann; Krueger, Joseph
Abstract : Background: CD20, a membrane B cell marker, is expressed on the majority of mature B cell neoplasms, including diffuse large B cell lymphoma and follicular lymphoma. Importantly, CD20 is the target of rituximab as well as autologous T cell and BiTE® therapies in clinical development. Studies show that one mechanism of resistance to rituximab-containing therapies is downregulation of CD20. 1 2 Development of an assay that provides highly sensitive and accurate detection of CD20 levels in the tissue context may help to assess whether there is a minimum CD20 threshold associated with response to rituximab or other CD20-targeted therapies. Here, we describe the development of a novel Quanticell™ assay for sensitive and quantitative detection of CD20 expression in formalin-fixed paraffin-embedded (FFPE) biopsy samples from NHL patients. Methods: A CD20 (Abcam, clone SP32) Quanticell-based assay, which utilizes Konica Minolta's novel fluorescent phosphor-integrated dots (PIDs) 3 was optimized on a panel of B lymphoma cell lines. Flow cytometry was performed to benchmark assay performance. Next, a human B lymphoma tissue microarray (TMA, n=39 cores) was stained using DAB-IHC to evaluate CD20 expression. Tumor cores (n=10) showing CD20highCD19high expression by DAB-IHC and immunofluorescence (IF)-IHC were selected for further evaluation. Human tonsil tissue was used to assess CD20 assay performance as a Quanticell singleplex or duplexed with CD19 IF-IHC. The TMA was stained with CD20 Quanticell plus CD19-AF488 to measure CD20 expression on a per cell basis. To assess sensitivity of CD20 Quanticell detection, a CD19 negative non-B cell core was analyzed. CD20 expression determined by Quanticell was compared to results generated with a commercially available method enabling digital profiling of CD20 protein in FFPE sections. Results: Analytical comparison between the Quanticell assay and flow cytometry on cell lines showed strong concordance between the two methods (CD20 Quanticell score versus CD20 receptor number). The Quanticell method demonstrated a broader dynamic range in CD20 expression in the TMA samples compared to DAB-IHC. Both the Quanticell and digital protein detection assays appropriately clustered cores into CD20low and CD20high categories. Notably, the CD20 Quanticell assay demonstrated the ability to measure CD20 expression accurately and precisely over a broader dynamic range when compared to the digital method. Conclusions: Relative to DAB IHC, the novel CD20 Quanticell assay provides significantly enhanced detection and quantification of CD20 in FFPE tissue samples. This technology may be useful to assess whether there are critical antigen densities associated with response to CD20-targeting therapies. Acknowledgements: The authors gratefully acknowledge technical assistance from Ankit Gandhi and Marie Zamanis. The authors also thank Sean Gerrin for technical writing review. Trial Registration: N/A Ethics Approval: N/A Consent: N/A References: Johnson NA, Boyle A, Bashashati A, et al. Diffuse large B-cell lymphoma: Reduced CD20 expression is associated with an inferior survival. Blood ; 2009;113:3773. Rasheed AA, Samad A, Raheem A, et al. CD20 expression and effects on outcome of relapsed/refractory diffuse large B cell lymphoma after treatment with Rituximab. Asian Pac J Cancer Prev 2018; 19: 331 Gonda K, Watanabe M, Tada H, et al. Quantitative diagnostic imaging of cancer tissues by using phosphor-integrated dots with ultra-high brightness. Sci Rep 2017;7:7509.